Konsep Rote Learning dan Meaningfull Learning alam Pendidikan Islam - Istikazah Martiana; Moh. Saleh; Era Mutiara Pratiwi; Gazi (Mataram University, 2026)
This study aims to analyze the concepts of rote learning and meaningful learning from an Islamic perspective and to examine the integration of both approaches in contemporary Islamic education. Islamic education faces challenges in creating learning processes that emphasize not only memorization but also understanding and reflection on Islamic values. Learning practices that are overly oriented toward memorization may result in superficial knowledge, while meaningful learning has not been optimally implemented. This study employs a qualitative approach using library research. The findings reveal that rote learning has legitimacy within the Islamic tradition, particularly in the practice of Qur’anic memorization (tahfidz Al-Qur’an) as an effort to preserve the authenticity of revelation. However, this approach needs to be balanced with meaningful learning, which aligns with the concepts of tafakkur and tadabbur. The integration of these two approaches represents an ideal model in Islamic education, where memorization serves as the foundation while understanding develops critical, reflective, and applicative thinking skills in real-life contexts.